Impact of sparse benthic life on seafloor roughness and high-frequency acoustic scatter - Mischa Schönke; Lars Wiesenberg; Inken Schulze; Dennis Wilken; Alexander Darr; Svenja Papenmeier; Peter Feldens (PANGAEA, 2019)
- recoded 200kHz backscatter multibeam data (HSX-file format) by a NORBIT iWBMSe multibeam echo sounder system (17 GB, 13 files) - recoded single beam acoustic data (SEGY) by the lander system (BENTHOWAVE INSTRUMENT INC) (50 MB, 17 files) - recoded point cloud optic data (.xyz-ASCII file) by the lander ULS 200 laser system (Robotics Inc.) (1 GB, 170 files) - Matlab script to preprocess optic data (.xyz-ASCII file) (10MB, 9 files) - Matlab script to preprocess acoustic data (SEGY) (11MB, 11 files)
Supplement to: Schönke, M et al. (2019): Impact of Sparse Benthic Life on Seafloor Roughness and High-Frequency Acoustic Scatter. Geoscience, 9(10), 454, https://doi.org/10.3390/geosciences9100454